Linkages among fluorescent dissolved organic matter, dissolved amino acids and lignin-derived phenols in a river-influenced ocean margin - Yamashita, Youhei; Fichot, Cédric G.; Shen, Yuan; Jaffé, Rudolf; Benner, Ronald (Frontiers in Marine Science, 2015)
Excitation emission matrix (EEM) fluorescence spectroscopy coupled with parallel factor analysis (PARAFAC) is commonly used to investigate the dynamics of dissolved organic matter (DOM). However, a lack of direct comparisons with known biomolecules makes it difficult to substantiate the molecular composition of specific fluorescent components. Here, coincident surface-water measurements of EEMs, dissolved lignin, and total dissolved amino acids (TDAA) acquired in the northern Gulf of Mexico were used to investigate the relationships between specific fluorescent components and DOM biomolecules. Two terrestrial humic-like components identified by EEM-PARAFAC using samples obtained from river to offshore waters were strongly linearly correlated with dissolved lignin concentrations. In addition, changes in terrestrial humic-like abundance were correlated with those in lignin phenol composition, suggesting such components are largely derived from lignin and its alteration products. By applying EEM-PARAFAC to offshore samples, two protein-like components were obtained. The tryptophan-like component was strongly correlated with TDAA concentrations, corroborating the suggested protein/peptide origin of this component. The ratios of tryptophan-like component to tyrosine-like component or dissolved organic carbon (DOC) concentrations were also correlated with DOC-normalized yields of TDAA, suggesting these proxies are useful indicators of the bioavailability of DOM in marine waters of the studied ecosystem.